Root growth dynamics and allocation as a response to rapid and local changes in soil moisture - S. Ceolin; S. Ceolin; S. J. Schymanski; S. J. Schymanski; D. van Dusschoten; R. Koller; J. Klaus (Biogeosciences)
Roots exhibit plasticity in morphology and physiology when exposed to fluctuating nutrient and water availability. However, the dynamics of daily timescale adjustments to changes in water availability are unclear, and experimental evidence of the rates of such adjustments is needed. In this study, we investigated how the root system responds within days to a sudden and localized increase in soil moisture (“hydromatching”). Root systems of maize plants were grown in soil columns divided into four layers by vaseline barriers and continuously monitored using magnetic resonance imaging (MRI) technology. We found that, within 48 h after application of water pulses in a given soil layer, root growth rates in that layer increased, while root growth rates in other layers decreased. Our results indicate local root growth was guided by local changes in soil moisture and potentially even by changes in soil moisture occurring in other parts of the soil profile, which would result in a coordinated response of the entire root system. Hydromatching in maize appears to be a dynamic and reversible phenomenon, for which the investment in biomass is continuously promoted in wet soil volumes and/or halted in drier soil volumes. This sheds new light onto the plasticity of root systems of maize plants and their ability to adjust to local and sudden changes in soil moisture, as would be expected due to patchy infiltration after rainfall or irrigation events.